Teacher's Decision-Making in Implementing Feedback in Senior High School (RETAIN, 2020)
In teaching-learning process, the teacher is required mastering not merely the subject knowledge but also the pedagogical knowledge. In dealing with feedback, the issue is the teacher deal with the effective and efficient action in fulfilling their roles as a teacher. To accomplish effective and efficient feedback, the teacher needs to create a right decision with a time restriction. Griffith, et al. (2013) proposed that the basic teaching skill is decision-making and every teaching act in class is the result of decisions. However, the teacher faces the time restriction in deciding the right feedback for their students. Therefore, the purpose of this research was to seek and describe the teacher's decision-making in implementing feedback. This research was designed as a qualitative research. The subjects of this research were four English teachers in senior high school. The semi structured interview was applied to get the data. Then, the results were analyzed and interpreted in the form of narrative and descriptive form. The findings have shown that the teacher's consideration in applying feedback is student's need, student's condition and teacher's belief. The teacher applied the decision-making rational and intuition. Keywords: teacher, decision-making, feedback.